2017
DOI: 10.1080/14786419.2017.1399387
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal properties of alpha-santalol, a naturally occurring constituent of sandalwood oil: review

Abstract: Alpha-santalol is a naturally occurring sesquiterpene that is derived from sandalwood oil. Its wide range of health benefits have been attributed to the modulation of various signalling pathways involved in the development of a particular disease. For example, the antitumour and cancer preventive properties of alpha-santalol have been shown to involve cell death induction through apoptosis and cell cycle arrest in various cancer models. A marked decrease in inflammatory markers have also been shown with alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Our observation that ESIO could specifically attenuate cAMP hydrolysis activity in an in vitro enzymatic assay in Figure 3B suggests that the suppressed cAMP hydrolysis activity by EISO or PDE-selective inhibitors in Figures 2 , 3A was due to an effect on the enzymes themselves. The concomitant decreased expression of transcript levels of the best annotated cAMP hydrolyzing PDE isoforms, PDE4 and 7, by EISO treatment is consistent with the known upregulation of PDE expression in response to inflammatory stresses ( Smith et al, 2004 ; Oger et al, 2005 ; Schafer et al, 2014 ) and previous reports that EISO is a potent anti-inflammatory agent ( Sharma et al, 2014 , 2017 ; Bommareddy et al, 2017 ). Our demonstration of the ability of EISO to modulate protein expression and distribution of PDE4 in organoids by IHC ( Figure 5 ) supports the observed EISO-mediated suppression of PDE4 transcription and indicates that EISO can suppress both activity and expression of PDE4 isoforms.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our observation that ESIO could specifically attenuate cAMP hydrolysis activity in an in vitro enzymatic assay in Figure 3B suggests that the suppressed cAMP hydrolysis activity by EISO or PDE-selective inhibitors in Figures 2 , 3A was due to an effect on the enzymes themselves. The concomitant decreased expression of transcript levels of the best annotated cAMP hydrolyzing PDE isoforms, PDE4 and 7, by EISO treatment is consistent with the known upregulation of PDE expression in response to inflammatory stresses ( Smith et al, 2004 ; Oger et al, 2005 ; Schafer et al, 2014 ) and previous reports that EISO is a potent anti-inflammatory agent ( Sharma et al, 2014 , 2017 ; Bommareddy et al, 2017 ). Our demonstration of the ability of EISO to modulate protein expression and distribution of PDE4 in organoids by IHC ( Figure 5 ) supports the observed EISO-mediated suppression of PDE4 transcription and indicates that EISO can suppress both activity and expression of PDE4 isoforms.…”
Section: Discussionsupporting
confidence: 89%
“…Natural products remain the best source for the development of new therapies because of their structural diversity and they do not match any source of small molecules ( Newman and Cragg, 2012 ). While widely used in aromatherapy, the essential oil from Indian sandalwood trees, Santalum album (Santalaceae) , commonly known as East Indian sandalwood oil (EISO), is a potent anti-inflammatory, antiseptic and astringent agent ( Burdock and Carabin, 2008 ; Sharma et al, 2014 ; Bommareddy et al, 2017 ), properties ideal for treatment of inflammatory skin disorders as has been reported for psoriasis ( Sharma et al, 2017 ) and acne ( Moy et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…EISO has been extensively used in aromatherapy as an antidepressant, to alter cogitation and psychological or physical wellness and is most likely used in fragrance material, incense, cosmetics, personal care products, meditative and spiritual practices. 1 , 2 Some preclinical and clinical research using an integrated approach has demonstrated that EISO and its active principles showed a broad spectrum of pharmacological activities, including chemopreventive, 3 5 antihyperglycemic, antioxidant, 6 antineoplastic, 7 , 8 antiviral 9 and anti-inflammatory activities. 10 , 11 However, the potential benefits of EISO treatment in preserving neural health and the underlying protective mechanisms from intracellular destructive stimuli and extracellular physiological changes are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ramadam et al reported the Melaleuca alternifolia EO (Tea tree oil, TTO) ability to induce cell cycle arrest at the G2/M phase of A375 cells [129], while in a previously published study, Beilharz's group described the TTO ability to elicit G1 cell cycle arrest in B16 cells [130]. In addition, α-santalol, the main component of Santalum album (Sandalwood oil) [154], in UACC-62 cells induced G2/M phase arrest through down-regulation of proteins critical for G2/M transition, such as cyclin A/Cdk2 and cyclin B/Cdc2 complexes, as well as microtubule depolymerisation. It also increased expression of wild-type p53 [155].…”
Section: Alteration Of Cell Cycle Distributionmentioning
confidence: 99%